(untitled) (Research, Society and Development, 2020)
Chronic diseases have a gradual onset, with a long or uncertain duration and generally have multiple causes, covering a wide category of diseases and requiring reorganizations of the health system. The health care network of people with chronic diseases seeks to promote comprehensive care and expand actions to promote health and prevent the appearance of complications. This study aimed to analyze the access of people with chronic non-communicable diseases to health services, comparing the provision of care and procedures in two small municipalities in the Health Region 29, in Rio Grande do Sul (RS), with the parameters established by the Ordinance 1.631/2015. It is a cross-sectional and exploratory study, based on documents from the Municipal Health Secretariats and interviews with managers and key informants from two municipalities in RS. It was found that there is no difficulty in accessing health services in primary care; however, the offer of assistance in medium and high complexity is insufficient, hindering user access and inducing their financial participation in the cost of diagnosis and treatment. It was concluded that it is necessary to expand the supply of medium and high complexity care, with regard to chronic diseases, and it is up to the three federative entities to establish mechanisms to guarantee access to these services, as well as qualified regulation.